Talking the talk and walking the walk How managers can influence the quality of work-life balance in a construction project - Bradley, L.; Brown, Kerry; Lingard, H.; Townsend, K.; Bailey, C. (Emerald, 2010)
Purpose – The construction industry in Australia is characterised by a long work-hours culture, with conditions that make it difficult for staff to balance their work and non-work lives. The objective of this paper is to measure the success of a work-place intervention designed to improve work-life balance (WLB) in an alliance project in the construction industry, and the role the project manager plays in this success. Design/methodology/approach – The paper focuses on an alliance case study. Interviews were conducted at two points in time, several months apart, after the interventions were implemented. Findings – Results showed that staff on the whole weremore satisfied with their work experience after the interventions, and indicated the important role that managers’ attitudes and behaviours played. Originality/value – Managerial support for work-life initiatives is a critical element in achieving WLB and satisfaction with working arrangements. The fact that the manager “talked the talk and walked the walk” was a major contributing success factor, which has not previously been demonstrated.